The Kinetics and Effect of pH on Removal of Manganese, Cadmium and Lead from Aqueous Solution by Maize Cobs (Global Journal of Science Frontier Research, 2012)
The ability of maize cobs as a biosorbent of Manganese Cadmium and lead in aqueous solution was studied. The effect of contact time, ionic strength, kinetic of sorption mechanism and the adsorbate concentrations on sorption of Mn 2+ , Cd 2+ , and Pb 2+ heavy metals were examined. The kinetic of the sorption mechanism of Mn 2+ , Cd 2+ and Pb 2+ was evaluated using pseudo-first order (Lagergren) rate and the second order (Ho-model) rate. The results indicate that pseudo-second order model provides a more appropriate description of the metals ions sorption in maize cobs. The adsorption capacities per unit gram of the adsorbent at equilibrium time, neutral pH, 200rpm, and 25 0 C temperature are 5.34 to 37.42 mg kg -1 for Mn 2+ , 2.50 to 19.79 mg kg -1 for Cd 2+ and 0.32 to 4.75 for Pb 2+ under10 to50 mg kg -1 initial metal concentration. Sorption equilibrium isotherm was determined and correlated with Langmuir and Freundlich model. It was found that the Freudlich adsorption model best fitted the isotherm data. It is concluded that maize cobs can be use as an effective adsorbent for removal of heavy metals from aqueous solution.
Keywords: Kinetics study; Cadmium; Manganese; Lead; maize cob; sorption